Contributions to the planning study for the implementation of a 5G access network in a dense urban area in Natal - da Luz Andrade Silva, Julia; Sizenando Rossiter Pinheiro, Fred; Soares da Silva, Gutenberg; A. De Sousa Jr., Vicente (Seven Editora, 2023)
Mobile access technology has undergone a major revolution and popularization in recent years. Each generation of mobile technology has provided significant performance improvements, with rapid changes in response to the demands of massively growing data traffic on mobile devices around the world. The fifth generation (5G) is built on three use cases: eMBB (Enhanced mobile bandwidth), URLLC (Ultra-reliable and low latency communication) and mMTC (Massive machine type communication). As the requirements of each use case are quite different, a 5G network of sufficient flexibility for the connectivity of existing and future services, which must be efficiently implemented in a single continuous block of spectrum or accurately in discrete blocks, using a carrier. The challenges for the evolution and deployment of 5G technology in Brazil regulatory and political issues, as well as the involvement of the effective network infrastructure. This case study presents performance results of a network evaluating the simulation of a 5G generation deployment scenario in a dense area in the city of Natal/RN, proposing a configuration formed by 4 macrocells operating at 700 MHz and a second network formed with addition of 39 microcells operating at 3.5 GHz. An evaluation carried out compares the results of coverage, SINR and capacity of both mobile networks, evaluating the challenges of transition from the current to the next generation of technology in face of the already existing access network infrastructure. The planned 5G network presented a performance compatible with what was expected in the NR standard, mainly in terms of capacity, as it reached rates around 100 to 200 Mbps in almost the entire coverage area. DOI: 10.56238/pacfdnsv1-063